Insecticides and Drought as a Fatal Combination for a Stream Macroinvertebrate Assemblage in a Catchment Area Exploited by Large-Scale Agriculture - Let, Marek; Špaček, Jan; Ferenčík, Martin; Kouba, Antonín; Bláha, Martin (My University, 2021)
This case study documents responses in a headwater macroinvertebrate assemblage to insecticide pollution and hydrological drought. In 2014, the Doubravka brook (Czech Republic) was damaged by a large overﬂow of a mixture of chlorpyrifos (CPS) and cypermethrin (CP). In 2016–2017, this brook was then affected by severe drought that sometimes led to an almost complete absence of surface water. We found signiﬁcant relationships between the strength of both these disturbances and the deeper taxonomic levels of both the overall macroinvertebrate assemblage (classes) and the arthropod assemblage alone (orders and dipteran families), as well as the functional feeding groups (FFGs). The CPS-CP contamination was mostly negatively correlated to arthropod and non-arthropod taxa and was positively correlated only with FFG collector-gatherers; on the other hand, the drought was negatively correlated to Simuliidae, Ephemeroptera, Trichoptera, and the FFG of grazer-scrapers and passive ﬁlterers. Drought conditions correlated most positively with Isopoda, Ostracoda, Heteroptera, adult Coleoptera, and predator and active ﬁlterer FFGs. The chosen eco-indicators (SPEARpesticides, SPEARrefuge, BMWP, and EPT) used as support information reveal the poor ecological status of the whole assemblage, including the control site, the cause of which is most likely to be the exploitation of the adjacent catchment area by large-scale agriculture. This type of agricultural exploitation will undoubtedly affect macroinvertebrate assemblages as a result of agrochemical and soil inputs during run-off events and will also exacerbate the effect of droughts when precipitation levels drop.
Insekticidy a sucho jako smrtelná kombinace pro tok hromadění makrobezobratlých v povodí využívané velkoplošným zemědělstvím
Keywords: headwaters; benthic species; chlorpyrifos; cypermethrin; organophosphate insecticide; pyrethroid insecticide; hydrological droughts; functional feeding groups; contamination; prameny; bentické druhy; chlorpyrifos; cypermethrin; organofosfátový insekticid; pyrethroidní insekticid; hydrologická sucha; funkční skupiny krmení; kontaminace